Towards a Decentralised European Public Prosecutor's Office?. Issue 1 (March 2013) - White, Simone
The author puts forward three models for the implementation of a European Public Prosecutor's Office, taking into account the legislative progress that has been made in the area of the European Criminal Law since the initial project was proposed in the late 1990s. She argues that the project is evolving towards a decentralised version of its former self, to fit in not only with legislative developments but also with the Zeitgeist, which calls for projects focussing resources on the EU Member States.